Age estimation for bowhead whales (Balaena mysticetus) using aspartic acid racemisation with enhanced hydrolysis and derivatisation procedures - Wetzel, D. L.; Reynolds, J. E.; Mercurio, P.; Givens, G. H.; Pulster, E. L.; George, J. C. (J. Cetacean Res. Manage., 2023)
Accurate determination of the ages of individual whales is key to developing effective conservation strategies for the bowhead whale (Balaena mysticetus). Previous attempts to develop reliable methods of age determination for this species have included using body length and baleen length measurements, baleen carbon cycling analysis, assessments of corpora accumulation, and aspartic acid racemisation (AAR; conversion of L to D enantiomers) measurements. Each of these methods has its limitations. The primary objective of this study was to improve the AAR analysis technique for determining age in bowhead whales in order to obtain consistent, reproducible results for D/L ratios for estimated ages. Using a modified AAR method, lenses from 68 bowhead whales were analysed and ages estimated. A comparison of the results to previous ageing by corpora counting or baleen carbon cycling methods for 11 of the whales showed smaller standard errors for the AAR analyses. The modified AAR methods applied in this study increase the precision of D/L measurements and provide improved bowhead whale AAR results.